The Concept Of Fatwa In The Perspective Of Islamic Law - Restu Annisa Ilma; Tria Adhelia; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
Fatwa works as guidelines for people For understand and apply Islamic teachings in an unavoidable situation in a way explicit set up in the Qur'an or Hadith, research This aiming For analyze fatwa concept in perspective Islamic law . The methods applied For analyzing the fatwa and its position in Islamic law is method qualitative with approach studies literature , review various source Islamic law . Approach This used Because research conducted​ including in category studies library . Research results show that the fatwa works as guidelines for people in face problem new that is not set up in a way explicit in the Qur'an and Hadith . Fatwas also reflect dynamics adaptive Islamic law to context social society . Fatwa does not only give solution to issues new , but also contribute to the development thinking Islamic law in general overall .